OCF Bridging Techniques for UWB/LoRa IoT Ecosystems - Hyun Seob Oh; Wha Sook Jeon; Dong Geun Jeong (IEEE Access)
The Open Connectivity Foundation (OCF) is one of the most powerful IoT standard organizations. The OCF has developed not only its own standard but also an open source software framework called IoTivity for efficient implementation of IoT systems. The OCF has made great efforts to develop the bridging techniques for supporting inter-operability with existing non-OCF IoT systems. In this paper, we develop the OCF-to-UWB (O2U) and OCF-to-LoRa (O2L) bridging techniques that can promote the release of diverse services related to UWB-based short-range and LoRaWAN-based long-range communications (e.g., indoor localization, sensor-based metering). We also suggest a simple and cost-effective bridging technique between different non-OCF IoT systems, which complies with the OCF standard. Our O2U and O2L bridging implementation is checked for consistency with the OCF standard using the OCF conformance test tool. Three example use-cases are implemented for demonstrating the usability of the developed O2U and O2L bridges, which are proximity-based Zigbee device control combined with UWB, LoRa-based metering, and LoRaWAN as backhaul of UWB system. Our work can provide a useful guideline to the development of new bridging techniques for other non-OCF IoT systems.